2021
DOI: 10.9734/jpri/2021/v33i60b35067
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Activity of Zinc Oxide Nanoparticle Synthesis Using Leaves Extract of Abies webbiana

Abstract: Aim: The present study aimed to analyse the cytotoxicity of zinc oxide nanoparticles (ZnO NPs) that are biosynthesized using extract of Abies webbiana Methodology: Zinc oxide nanoparticles were synthesized by green approach using A. webbiana and were characterized by UV- vis spectroscopy. The powdered A. webbiana mediated ZnO NPs were subjected to cytotoxic tests for different concentrations by brine shrimp lethality assay. Results: ZnO NPs synthesized from A. webbiana showed reduced toxicity at lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Although there were no fatalities observed at greater dosages, this underscores that the cytotoxic effect is a dose-dependent effect [ 18 ]. Moreover, green-synthesised ZnONPs using C oriander oleoresin demonstrated promising outcomes in cytotoxicity assessments, showcasing reduced toxicity levels [ 19 ]. In addition, findings indicated that ZnONPs produced from Abies webbiana show less toxic effects comparatively.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were no fatalities observed at greater dosages, this underscores that the cytotoxic effect is a dose-dependent effect [ 18 ]. Moreover, green-synthesised ZnONPs using C oriander oleoresin demonstrated promising outcomes in cytotoxicity assessments, showcasing reduced toxicity levels [ 19 ]. In addition, findings indicated that ZnONPs produced from Abies webbiana show less toxic effects comparatively.…”
Section: Discussionmentioning
confidence: 99%
“…While there is no fatality rate at higher dosages, this demonstrates that the cytotoxic impact is dose-dependent [ 20 ]. Furthermore, the green-synthesized ZnONPs derived from coriander oleoresin showed encouraging results in cytotoxicity tests as they exhibited lower toxicity [ 21 ]. The results also revealed that ZnONPs synthesized from Abies webbiana are less toxic.…”
Section: Discussionmentioning
confidence: 99%